2017
DOI: 10.1097/j.pain.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Spinal intracellular metabotropic glutamate receptor 5 (mGluR5) contributes to pain and c-fos expression in a rat model of inflammatory pain

Abstract: Metabotropic glutamate receptor 5 (mGluR5) is an excitatory G-protein-coupled receptor (GPCR) present in the spinal cord dorsal horn (SCDH) where it has a well-established role in pain. In addition to its traditional location on the cytoplasmic membrane, recent evidence shows that these receptors are present intracellularly on the nuclear membrane in the spinal cord dorsal horn and are implicated in neuropathic pain. Nuclear mGluR5 is a functional receptor that binds glutamate entering the cell through the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“… 12 Accumulating evidence suggests that mGluR5 is a crucial mediator of glutamate-induced neuroplasticity underlying persistent pain. 46 50 Since blocking P2X4 or TrkB receptors prevents the upregulation of EAAT3 and trigeminal allodynia, pharmacological blockade of these receptors may represent a potential therapeutic approach for treating trigeminal allodynia, as seen in migraineurs. More studies are needed to further investigate the precise mechanisms underlying microglia-neuron interactions in the pathophysiology of chronic migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Accumulating evidence suggests that mGluR5 is a crucial mediator of glutamate-induced neuroplasticity underlying persistent pain. 46 50 Since blocking P2X4 or TrkB receptors prevents the upregulation of EAAT3 and trigeminal allodynia, pharmacological blockade of these receptors may represent a potential therapeutic approach for treating trigeminal allodynia, as seen in migraineurs. More studies are needed to further investigate the precise mechanisms underlying microglia-neuron interactions in the pathophysiology of chronic migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate influx through EAAT3 may further activate intracellular metabotropic glutamate 5 receptor (mGluR5), which is essential for enhanced Ca 2+ -dependent Fos and plays a crucial role in the glutamate-induced neuroplasticity underlying persistent pain. 12 , 46 50 …”
Section: Discussionmentioning
confidence: 99%
“…Using permeable mGlu5 antagonists reaching the cytoplasm, the authors have demonstrated that blocking intracellular mGlu5 had a greater antinociceptive effect than by blocking cell membrane expressed mGlu5 (Vincent et al, 2016). Pre-treatment with an excitatory amino acid transporter (EAAT) inhibitor, which is meant to decrease intracellular glutamate levels, decreases pain-related behavior in an inflammatory pain model (Vincent et al, 2017).…”
Section: Role Of Mglur In Pain Transmission At the Spinal Cord Levelmentioning
confidence: 99%
“…An increasing body of evidence suggests that glutamatergic mechanisms and glutamate receptors are involved in the regulation of pain, i.e. pain transmission [16].…”
Section: Discussionmentioning
confidence: 99%